Sentinel Lymph Node Biopsy vs. Elective Neck Dissection in Patients with T1/T2 N0 Oral Squamous Cell Carcinoma: A Matched Pair Analysis - Guilherme Machado de Carvalho; Vanessa Gonçalves Dias; Hugo Kohler; Carlos Takahiro Chone; Alexandre Caixeta Guimarães; Agrício Nubiato Crespo (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Background: The management of the clinically and radiological negative neck in patients with early squamous cell carcinoma of head and neck (HNSCC) is still controversial. As approximately 20 to 30% of these patients harbor occult neck disease, most of them is submitted to elective neck dissection with no benefit in great majority of those cases. Sentinel lymph node biopsy (SLB) is a potential method for staging of lymphatic metastasis in HNSCC and the status of the sentinel node predicts the presence of metastasis in the remainder of the nodes within the nodal basin. Objective: To evaluate the neck recurrence rate of patients with early stage (T1/T2) HNSCC of the oral cavity with clinically negative necks (cN0), in patients submitted to sentinel lymph node biopsy (SNB) or elective neck dissection (END). Methods: Clinical retrospective comparison of two patient cohorts of early stage oral cancer tested for primary tumor resection and SNB without subsequent END or primary tumor resection with END. Those comparisons were made by a matched pair analysis. Results: The current study included 52 patients with early stage oral cancer; 30 in the SNB group and 22 in the control group (END). Both SNB and END groups had similar performance regarding the recurrence rate of neck, without significant difference between both groups. Conclusion: Neck recurrence rates were similar between groups of patients in which SNB or END was performed.